Effect of auxin types on in vitro and ex vitro rooting and acclimatization of grapevine as influenced by substrates - Barreto, M. S.; Nookaraju, A. (Indian Journal of Horticulture, 2007)
Transferring micropropagated plantlets from in vitro to in vivo conditions is a critical step because plantlets have under-developed cuticle and stomata which result in wilting due to low humidity, fungal attack and bleaching in high light intensities. The resumption of terminal growth indicates successful establishment which is a change from mixotrophy to autotrophy. The survival of Vitis vinifera cvs. 2A-Clone and Red Globe plantlets rooted in vitro was 86.66 and 83.33%, respectively and the established plants showed a well-defined root system. Plantlets rooted in vivo by auxin pulse were easier to transfer and acclimatize with a survival percentage of 96.66 and 79.92 for 2A-Clone and Red Globe, respectively but the rooting was of fibrous type with few main roots and less number of root hairs. Coco-peat in combination with sand and soil was better for quick acclimatization and establishment (97.5 and 95% survival for 2A-Clone and Red Globe respectively) of the micropropagated plantlets.
Keywords: auxin pulse; coco-peat; grape; micropropagation; plantlet survival